A review: Sustainable practices in specialty yarn manufacturing - Tusief, Dr. Muhammad Qamar; Irshad, Attia; Waheed, Fehmeeda; Afzal, Minahil; Abdullah, Muhammad (ACADEMIA International Journal for Social Sciences, 2025)
The specialized yarn sector is swiftly evolving to accord with sustainable methods propelled via ecological issues and customer desires for ecologically safe resources. Specialty sustainable yarns unite aesthetics, functionality, and ecological awareness [7]. Innovations feature using certain green fibers such as cotton, hemp, and reused things [16], with specific new spinning ways like air jet spinning and 3D knitting. Yarn's clever technologies and AI customization increase performance and reduce waste, while circular initiatives promote recycling and closed-loop output [16]. These yarns have applications throughout industries, from high fashion and home textiles to vehicular and medical fabrics. Even with problems such as high expenses, supply chain difficulties, and greenwashing, the market for sustainable yarns keeps growing because of increased consumer awareness as well as regulatory pressure. A portion of the industry's future lies in certain biotech innovations and diverse regenerative fibers. Another portion of the industry's future lies in certain smart functionalities, with increased emphasis on digital transparency and zero-waste manufacturing. By incorporating sustainability in each phase of production, the specialty yarn sector is designed to change textiles via a greener and more advanced approach.